Effective Water Use Required for Improving Crop Growth Rather Than Transpiration Efficiency - Sinclair, Thomas R. (Frontiers in Plant Science, 2018)
The phenomenological expression showing crop yield to be directly dependent on crop transpiration use efficiency (TE) has encourage continued focus on TE as a viable approach to increasing crop yields. The difficulty in the phenomenological perspective is that research tends not to match with the underlying mechanistic variables defining TE. Experimental evidence and the mechanistic derivation of TE by Tanner and Sinclair show that the common focus on increasing the intrinsic ratio of leaf CO2 / H2O exchange has limited opportunities for improvement. On the other hand, the derivation showed that daily vapor pressure deficit (VPD) weighted for the daily cycle of transpiration rate has a large, direct impact on TE. However, VPD is often viewed as an environmental variable although daily weighted VPD can be under plant control as a result of partial stomatal closure during the midday. Such partial stomatal closure results in decreased weighted VPD and transpiration rate, there can be substantial conservation of soil water. The conserved soil water allows sustained physiological activity during subsequent periods of developing water deficits, which can be especially beneficial during reproductive development. The shift in the temporal dynamics of water use by water conservations traits has been shown in simulation studies to result in substantial yield increases. It is suggested from this analysis that effective water use through the growing season is more important for increasing crop yield than attempts focused on improving the static, intrinsic TE ratio.